The Influence of Murabahah, Mudharabah, and Musyarakah on the Profitability of Islamic Banking - Murni Nia; Abdul Rachman Rika; Asriyani Mulia Basri; Murniati Murniati; Wahyu Muh Syahta (Al-Qalam Institute, 2026)
This study examines the effect of murabahah, mudharabah, and musyarakah financing on the profitability of Islamic commercial banks registered with the Financial Services Authority (OJK) during the 2021–2023 period. Previous studies have reported inconsistent findings regarding the relationship between Islamic financing contracts and bank profitability, particularly in the context of participatory financing schemes in Islamic banking institutions. This study contributes to the literature by providing empirical evidence on the comparative influence of major Islamic financing contracts on profitability using quarterly multi-bank data from Indonesia. The study employs a quantitative approach using purposive sampling, resulting in three Islamic commercial banks as research samples: PT Bank Muamalat Indonesia, PT Bank Victoria Syariah, and PT BCA Syariah. Data were analyzed using multiple linear regression analysis. The findings reveal that murabahah financing has a negative and significant effect on profitability, mudharabah financing has a positive but insignificant effect, while musyarakah financing has a positive and significant effect on profitability. Simultaneously, murabahah, mudharabah, and musyarakah financing collectively have a significant influence on the profitability of Islamic commercial banks. These findings indicate that financing portfolio composition plays an important role in shaping the financial performance of Islamic banking institutions and highlights the importance of balancing fixed-margin and profit-sharing financing schemes to achieve sustainable profitability.